Comparative Literature in the Turkish Context: Past, Present and Possible Trajectories - Mustafa Kirca; H. Baktir (Comparative Literature: East & West)
This article aims to offer a concise analysis and evaluation of the historical trajectory and the current state of comparative literature in Turkey with a particular focus on its interdisciplinary nature. Additionally, it seeks to explore the development of comparative literature and translation studies in the Turkish context, aiming to reassess the seemingly close relationship between these adjacent fields within the context of Turkish literature, which can, we believe, encourage border-crossings in comparative and translation studies and open a space for newfangled approaches in comparative studies of translated literature.